The Term Wave Console: Reimagining Console Communication - Maniraj, V; Manohari, E (International Journal of Computer Sciences and Engineering, 2025)
Throughout human civilization, content has been an indispenscapable channel of communication. Modern computers equipped with desktop consoles have dramatically increased the ease and volume of text-based communication in the structure of email, content chat, and Web posting. As computing advances expanded beyond the confines of the desktop, the need on the other hand compelling content section on versatile gadgets has been increasingly felt over the last two decades. Such a need has inspired both scholarly researchers and the information innovation industry in pursuit of compelling content section techniques elective to the ubiquitous desktop keyboards.